Intervention or Collaboration? Redesigning Information and Communication Technologies for Development. - Bon, Anna (2020)
How can we design and build digital technologies to support people in poor and low resource environments to achieve their objectives? And how can we do this inclusively and ethically, while considering the complexity of their living and working environments? This is the central question in my research. One of the grand challenges of international development cooperation is to make digital technologies available for social and economic development of poor regions of the world. To achieve this goal – often referred to as ICT4D – knowledge and technologies are transferred from wealthy countries to poor regions. Nevertheless, these efforts have often turned out unsuccessful and unsustainable, despite large budgets and numerous projects in prestigious international development programs. Mismatch between the transferred technologies and the target environment is a recurrent problem of ICT4D projects. Improvement can be achieved, for example, by involving end-users in the design process. International development organizations are aware of this, and terms like "co-creation", "participation" and "user-oriented design" have nowadays become part of the international development discourse. However, real co-creation and user-centered design are incompatible with unidirectional transfer of technologies and knowledge (this is how ICT4D is commonly organized, in conventional international development). Moreover, the term participation becomes meaningless, in the light of externally formulated development goals. One key question to ask is: what do the envisaged users want? Remarkably, many ICT4D projects, programs and policies do not really ask and (field) investigate this question, which can only be answered by extensive research on-the-ground. This thesis describes the search for and the design of an alternative approach to ICT4D. Ten years of field and action research with partners in Mali, Burkina Faso, and Ghana have led to a collaborative, iterative and adaptive approach, dubbed "ICT4D 3.0". What is novel of this alternative approach and how does it answer the central question? First of all, ICT4D 3.0 is a practical approach for critical investigation and action. It consists of a reconfigurable framework that guides the design and development of information systems, bridging the knowledge gap between developers and users to unlock and integrate different domains of (global, local, indigenous, academic, nonacademic) knowledge. It targets complex, resource-constrained environments where many (for the ICT developers and researchers) unfamiliar conditions or obstacles may exist. It fosters innovative capacity and learning in action, bringing together people with different backgrounds and perspectives in trans-disciplinary and multicultural teams. It is socio-technical, result-oriented, focused on the objectives of the stakeholders and the requirements of their livelihoods. This approach has been validated in various different contexts, by users, ICT developers, practitioners and students. Second, ICT4D 3.0 contributes to a theoretical understanding of ICT4D as a process of networked innovation in complex (adaptive) systems. The underlying idea is that knowledge sharing and diffusion of innovations are complex (non-linear) dynamic processes that evolve and propagate through social networks in rather unpredictable ways, whereby innovation works out differently, depending on context, and whereby contextual (e.g. social, cultural, environmental, political) factors play an important role, and have to be considered. This theoretical framework explains the effectiveness of a collaborative, iterative, adaptive approach in ICT4D. Third, ICT4D 3.0 is built on ethical principles. When reflecting on the meaning and purpose of digital development, it is clear that digital development is not only a question of technology and practice, and collaboration is more than a prerequisite for successful technological innovation and long-term sustainability: collaboration is a fundamental human, ethical value. Therefore, as a reflective practitioner, one has to ask oneself whose interests one is actually looking after, which goals one is trying to achieve, where they come from, how power and political issues play a role and which core values are at stake. This makes ICT4D 3.0 into a democratic process of dialogue and deliberation, in which all voices are heard, in which the local context and complexity are central and in which development goals are determined by the users themselves and not imposed from outside. In this light, the approach proposed in this thesis takes a value position and can be considered a decolonial approach, striving for democracy, emancipation, autonomy and social and economic betterment. Field experience shows that ICT4D can be a meaningful, collaborative, networked process of knowledge sharing, driven by local initiatives, realizing change for the better, in a complex world.

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.

Navigating by Judgment: Organizational Structure, Autonomy, and Country Context in Delivering Foreign Aid - Honig, Daniel (Harvard University, Graduate School of Arts & Sciences, 2015)
This dissertation examines when initiatives by International Development Organizations (IDOs) are more, and less, successful. The core argument is that allowing field-level agents to drive initiatives – what I call organizational Navigation by Judgment – will often be the most effective way to deliver aid. This inverts what a classical application of the principal agent model – the workhorse of studies of public management and bureaucracy – would predict, with better performance resulting from less control. In the delivery of foreign aid the costs of monitoring to the principal are often overshadowed by the deleterious effects of the monitoring itself. The core of the argument is that development implementation requires soft information, tacit knowledge, and flexibility that are crowded out by tight controls or an organizational navigation strategy focused on short term measurement and targets. As a result there are increasing returns to Navigation by Judgment in environments that are uncertain or difficult to understand from the outside and tasks where outputs are difficult to observe and/or poorly correlated with long term intervention goals. Insecure political authorizing environments which constrain the autonomy of IDOs prevent these organizations from Navigating by Judgment in situations where this is the best strategy. Empirically, this dissertation examines a cross-IDO dataset of projects (including over 14,000 projects over 50 years over 9 organizations), which I have assembled. It also examines eight cases of development interventions in Liberia and South Africa. These cases are matched pairs comparing the performance and navigation strategies of the US Agency for International Development (a low autonomy IDO) and the UK’s Department for International Development (a higher autonomy IDO) in capacity building and health sector interventions.
Keywords: IMPORTANT

Managing Upward and Downward Accountability in an International Development Project - A Case Study of a World Bank Telecommunications Infrastructure Project in Benin - Kolker, Eva; Kulldorff, Catharina (Master's Thesis, Stockholm School of Economics, 2013)
Keywords: Downward accountability; Upward accountability